The Shift in Money Recognition in Indonesia: The Impact of Inflation, Interest Rates, and Innovation in Digital Payment Systems - May Husnul Khotimah; Muh. Rudi Nugroho (Moneter: Jurnal Keuangan dan Perbankan, 2026)
This study estimates the dynamics of money demand in Indonesia by integrating inflation, interest rates, and electronic money (e-money). Utilizing the Error Correction Model (ECM), this research analyzes both long-run and short-run dynamics, emphasizing the role of digitalization. The results indicate that in the long run, inflation, interest rates, and e-money exert positive and significant effects on money demand. Higher inflation drives transaction-driven liquidity, while the positive impact of interest rates reflects a precautionary motive amid economic uncertainty. Additionally, e-money complements physical currency by accelerating the velocity of money. Conversely, the short-run ECM estimations show no significant effects, confirming an adaptation lag to macroeconomic and technological changes before reaching equilibrium. Overall, long-term transactions and digital payments remain the primary drivers of money demand. Therefore, monetary authorities must maintain price and interest rate stability while strengthening digital payment infrastructure to support national economic stability.